1998
DOI: 10.1017/s0014479798343057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Time on Weed Seedling Emergence and Nutrient Release in Cattle Manure

Abstract: An experiment to determine weed spectrum, weed seedling numbers, temperature and nutrient changes in manure heaped for one to five months was undertaken over two seasons. Weed seedling numbers in manure heaped for one to five months decreased significa ntly by 65–70%. The weed spectrum comprised 17 broadleaf weed species of which Amaranthus hybridus, Leucasmartinicensis and Nicandra physalodes were most prevalent. There were six grasses with Eleusine indica and Cynodon dactylon being dominant. Temperature inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The presence and survival of P. aviculare and C. arvensis were not influenced by the type or rate of fertiliser applied (Table 3). Composting did not prompt a significant increase in the presence of these weed species, probably because the compost was mature enough to have eliminated the germinative power of any species it might contain, as was suggested by Rupende et al. (1998) and Ozores‐Hampton et al.…”
Section: Resultsmentioning
confidence: 90%
“…The presence and survival of P. aviculare and C. arvensis were not influenced by the type or rate of fertiliser applied (Table 3). Composting did not prompt a significant increase in the presence of these weed species, probably because the compost was mature enough to have eliminated the germinative power of any species it might contain, as was suggested by Rupende et al. (1998) and Ozores‐Hampton et al.…”
Section: Resultsmentioning
confidence: 90%
“…These strategies include proper housing and storage of manure, adding bedding to both the faeces and urine in the kraals, supplementing the animal feed, composting and proper handling of the manure in the field. Rupende et al (1998) have shown that compositing not only improves the nutrient content, but also kills weed seeds in the manure. These aspects need to receive much attention in order to improve the management of the available manure resources in this challenging agroecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Also, soil pH in salamander refugia was relatively alkaline in our study area (n = 27, mean 7.52, range 5.3-8.9, SD = 1.00; Hasumi et al 2009), and downed logs harboring S. keyserlingii at Darhadyn had alkaline soil with mean pH of 8.56 (n logs = 40, n measurements = 559, range 7.07-9.13, SD = 0.24; M. Hasumi, T. Hongorzul, and M. Nakagawa, unpublished data). We suspect that alkalinity of the water and soil in Mongolian wetlands heavily depends on excrement from a great number of livestock animals, as demonstrated in many agricultural fields with livestock (especially cattle) grazing (e.g., Banik et al 1996;Rupende et al 1998;Kurz et al 2006). This is likely because water pH in site 5 used frequently for watering livestock (mean 10.45, range 10.1-10.7, SD = 0.19), where their excrement might be deposited, was the greatest of six sites examined.…”
Section: Discussionmentioning
confidence: 99%